Antibody elution from red blood cells. Issue 1 (January 1963) - Rubin, Harry
Abstract : An elution technique is described which gives eluates at least as potent as previously described methods. Elution can be completed in only 15 minutes. The method, a modification of that of Vos and Kelsall, is simple to carry out and requires the minimum of equipment. Studies have shown that the coating antibody is almost, but not completely, eluted.